An introduction to Stein's method - Barbour, A. D.; Chen, Louis H. Y. (Louis Hsiao Yun), 1940- (Lecture notes series (National University of Singapore. Institute for Mathematical Sciences) ;, 2005)
A common theme in probability theory is the approximation of complicated probability distributions by simpler ones, the central limit theorem being a classical example. Stein's method is a tool which makes this possible in a wide variety of situations. Traditional approaches, for example using Fourier analysis, become awkward to carry through in situations in which dependence plays an important part, whereas Stein's method can often still be applied to great effect. In addition, the method delivers estimates for the error in the approximation, and not just a proof of convergence. Nor is there.